[Investigation of transcription factor Brachyury (T) expression in human normal and tumor tissues]. - Krukovskaia, L L; Polev, D E; Nosova, Iu K; Baranova, A V; Koliubaeva, S N; Kozlov, A P (Voprosy onkologii, 2008)
By using computational differential display approach we identified a number of UniGene clusters which comprised 90% or more of ESTs from tumor cDNA libraries. One of them was cluster Hs.389457 which corresponds to the human gene Brachyury (T). That encodes a T-box gene family member transcription factor which is pivotal in early embryonal development. To experimentally verify our in silico findings of T expression, PCR was conducted using panels of cDNA from various human normal and tumor tissues. According to our results, Brachynry is expressed in tumors of the digestive tract, testis, ovary, breast, kidney, bladder, lung and brain tunic as well as in lymphomas. Weak amplification signals were picked up from normal tissues of small intestine, spleen and testis. Our results support earlier hypothesis on predominant tumor-related expression of Brachyury gene in adults.
Keywords: Breast Neoplasms; DNA, Complementary; DNA, Neoplasm; Female; Fetal Proteins; Gene Expression Regulation, Neoplastic; Genital Neoplasms, Female; Head and Neck Neoplasms; Humans; Lung Neoplasms; Lymphoma; Male; Neoplasms; T-Box Domain Proteins